The effect of friction spot stir welding in installing rivet double cover lap joints on 7075–T6 aluminum plate on shear strength - Sehono, Sehono; Sitopu, Aseng Franslee (Jurnal Polimesin, 2023)
FSSW is a variation of FSW developed in metal processes. The principle of FSSW is rotating an object that is wear-resistant and then rubbed with a plate joint. The use of FSSW can be utilized in the installation of rivets such as in the drilling process, so this process needs to be investigated. This is because the heat caused by rotation will change the mechanical properties of the material so further research is needed. In this study, a connection performance comparison was made between the FSSW method and the drill. The plate used is aluminum 7075-T6 with a lap joint connection type. To find out each performance, a shear test, hardness test, and metallographic test were carried out. From the results of the shear strength test, it can be concluded that the FSSW variation is the best with an average shear strength value of 755,190 MPa, while the drill variation has an average shear strength value of 470,227 MPa. The average value for drill variations in the HAZ area was 185.06 while for the FSSW variation, it only reached 147.75. The macro test results proved that the cause of the shear strength in the FSSW was greater than that of the drill, this was caused by the difference in the size of the rivet diameter due to the use of a bad rivet gun. Meanwhile, based on the results of micro photos, the size of the structure in the HAZ area will be relatively longer than the RAW section, this is caused by friction between the tool and the workpiece